Methodological notes on the complex linguofolkloristic analysis of the poetics of the Methodius's translation of the Song of Songs - Дядищева-Росовецька, Юлія Борисівна (Київський національний університет імені Тараса Шевченка, 2021)
The article is devoted to some methodological issues that arise in the linguistic and folklore analysis of the poetics of the Methodius's translation of the Song of Songs, which we consider as an orally poetic text, later elaborated in literature. The parameters of interlingual, interfaith and interethnic transmission under conditions of considerable time duration are outlined. Problems related to layers not only temporal, but also within several ethnic traditions, namely: ancient Egyptian, ancient Jewish, ancient Greek, ancient Slavic. There are a number of tropes and stylistic figures that are used as a means of organizing the text or used as components for stylistic symmetry. These are permanent epithets, different types of repetitions, anaphora and epiphora, tautological combinations, pleonastic combinations, allegories, comparisons, ekphrasis, specific composites, etc. It is possible to involve in the study of common in folklore hyperbole, personifications, paraphrases. The range of methodological difficulties is outlined. The article warns about the counterproductiveness of the study of literary tropes in isolation from the contexts of specific works, in the abstract non-ethnic continuum, although in synchrony and diachrony. If in the national literatures, especially in the early stages of their development, there are peculiar genre systems, then in folklore there are differences in genres of even related ethnic groups. Hence, the need to take into account the differences between the genres of wedding poetry in ancient Aramaic folklore and in the oral traditions of the peoples whose scribes translated the poem. The importance of a specific contextual study of the tracks of the Song of Songs is emphasized, because the movement of its texts in time and space is a change in their perceptions by translators, editors, transcribers, which leads to changes in understanding and aesthetic acceptance of the monument by readers. It is stressed that the full picture can be obtained only by examining all the national and ethnic branches of the family tree of the monument. The question of place in such a comprehensive study of religious allegorical and symbolic interpretations is also delivered in the article.

Статтю присвячено деяким методологічним питанням, що виникають при лінгвофольклористичному аналізі поетики Мефодіївського перекладу Пісні над Піснями, яку розглядаємо як текст усно-поетичний, згодом опрацьований літературно. Окреслено параметри міжмовної, міжконфесійної та міжетнічної трансмісії за умов значної тяглості в часі. Визначено проблеми, пов'язані з нашаруваннями не тільки темпоральними, але і в межах кількох етнічних традицій, а саме: давньоєгипетської, давньоєврейської, давньогрецької, давньослов'янської. Виділено ряд тропів та стилістичних фігур, що використовуються як засоби організації тексту або вживаються як компоненти для стилістичної симетрії. Це постійні епітети, різні типи повторів, анафор та епіфор, тавтологічних сполучень, плеонастичних сполучень, алегорії, порівняння, екфрасиси, специфічні композити тощо. Можливе залучення до дослідження поширених у фольклорі гіпербол, персоніфікацій, перифразів. Окреслено коло методологічних труднощів. Застережено щодо контрпродуктивності вивчення тропів у відриві від контекстів конкретних творів, в абстрактному позаетнічному континуумі, хоч і в синхронії та діахронії. Якщо в національних літературах, особливо на перших етапах їх розвитку, існують своєрідні жанрові системи, то й у фольклорі спостерігаються відмінності в жанрах у навіть споріднених етносів. Звідси необхідність врахування відмінностей між жанрами весільної поезії в давньому арамейському фольклорі та в усних традиціях народів, чиї книжники перекладали поему. Наголошено на важливості конкретного контекстуального вивчення тропів Пісні над Піснями, адже рух її текстів в часі та просторі – це зміна сприймань їх перекладачами, редакторами, переписувачами, що призводить до зрушень у розумінні та естетичному прийнятті пам'ятки читачами. Підкреслено, що повну картину можна отримати, лише дослідивши всі національні та етнічні гілки генеалогічного древа пам'ятки. Поставлено питання про місце в такому комплексному дослідженні релігійних алегорично-символічних тлумачень.
Методологічні замітки до комплексного лінгвофольклористичного аналізу поетики Мефодіївського перекладу Пісні над Піснями
Keywords: methodology; lingvofolkloristics; lingvostylistics; poetics; Song of Songs; bibleistics; tropes.; методологія; лінгвофольклористика; лінгвостилістика; поетика; Пісня над Піснями; бібліїстика; тропи.